1984
DOI: 10.1093/infdis/149.2.245
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Yersinia pseudotuberculosis Infection

Abstract: Nineteen patients were involved in an outbreak of infection caused by Yersinia pseudotuberculosis serotype 3. No epidemics attributable to this microorganism have been previously reported; the most extensive known cluster of cases involved four children in one family and their pet dog. The key finding in the outbreak described in the present study was the bacteriologic identification of serotype 3 in stool specimens from patients with clinically typical yersiniosis. Twelve cases were identified by isolation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 13 publications
5
38
1
2
Order By: Relevance
“…In the human, Y. pseudotuberculosis causes varying degrees of illnesses from diarrhea and abdominal pain to more systemic symptoms such as fever, scarlatiniform skin rash, conjunctivitis, erythema nodosum, and lymphadenopathy (1)(2)(3). Complications of reactive arthritis, acute uveitis, coronary aneurysms, and acute renal failure are not infrequently reported (4)(5)(6)(7)(8). The mechanisms by which the organism mediates these symptoms are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the human, Y. pseudotuberculosis causes varying degrees of illnesses from diarrhea and abdominal pain to more systemic symptoms such as fever, scarlatiniform skin rash, conjunctivitis, erythema nodosum, and lymphadenopathy (1)(2)(3). Complications of reactive arthritis, acute uveitis, coronary aneurysms, and acute renal failure are not infrequently reported (4)(5)(6)(7)(8). The mechanisms by which the organism mediates these symptoms are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…We experimentally induced deletion of the ypm gene from a superantigen-expressing Y. pseudotuberculosis: using the association of aph(3)-IIIa and sacB genes, we demonstrated that when these reporter genes were present in the ypm locus, deletion of these genes was about 250 times more frequent than when they were located in another region of the Y. pseudotuberculosis chromosome. These results indicate that unlike other superantigenic toxin genes, the Yersinia ypm genes are not associated with mobile genetic elements but are inserted in an unstable locus of the genome.Yersinia pseudotuberculosis, a microorganism causing gastrointestinal diseases and immunopathological complications such as reactive arthritis and erythema nodosum (10,47,59,60), is at present the only gram-negative bacteria known to produce a superantigenic toxin. This molecule (designated YPM for Y. pseudotuberculosis-derived mitogen) is a 14.5-kDa protein able to induce proliferation of human T lymphocytes bearing V␤3, V␤9, V␤13.1, and V␤13.2 T-cell receptor variable regions (1, 61).…”
mentioning
confidence: 99%
“…Karın ağrısı, ateş ve kusma mezenterik lenf adenitin en sık gözlenen klinik bulgularıdır. Bu bulgular apandisitin de benzer bulgularıdır 2,3,11 . Ancak YP enfeksiyonuna bağlı karın içi kitle yapan mezenterik adenit durumu çok az sayıda raporlanmıştır, ancak genellikle bu kitleler sağ alt kadranda olup apandisit ile karışmaktadır.…”
Section: Discussionunclassified
“…Akut gasroenteritlerde YP'e, Salmonella ve Campylobacter'den daha sık karşılaşıldığı bildirilmektedir 1 . YP enfeksiyon'u genellikle akut gastroenterit ve mezenterik lenfadenite neden olur ve mezenterik lenfadenit durumunda akut apandisit kliniğine benzer bulgular verir 2,3,4 . Fakat karında kitle nadir olarak bildirilen bir durum olup bu da genellikle sağ alt kadranda tespit edilir 2,5 .…”
Section: öZetunclassified